POTENSI SALVINIA MOLESTA D.S. MITCHELL, LIMNOCHARIS FLAVA (L.) BUCHENAU DAN MONOCHORIA VAGINALIS (BURM.F.) PRESL UNTUK FITOEKSTRAKSI MERKURI DI SAWAH YANG TERCEMAR MERKURI AKIBAT KEGIATAN PENAMBANG EMAS TANPA IZIN (PETI) - Juhaeti, Titi; Hidayati, Nuril; Syarif, Fauzia; Hidayat, Syamsul (Jurnal Teknologi Lingkungan, 2010)
The research were carried out to study the potency of Salvinia molesta D.S. Mitchell (Kiambang), Limnocharis flava (L.) Buchenau (Genjer) and Monochoria vaginalis (Burm.f.) Presl (Eceng) for Hg phytoextraction on paddy field contaminated with Hg from illegal mining. The plants were grown on contaminated media from paddy field in Pongkor (68.269 ppm Hg) added by NPK fertilizer (0, 3 and 6 g/pot) and ammonium thiosulphate chelating agent (0, 20 ppm). The result showed that the growth of kiambang,eceng, genjer and padi are significantly different. Chelating agent did not significantly affect the plant growth, meanwhile fertilizer significantly affected the plant growth. Thetreatments resulted in different Hg concentration in the plants. Fertilizer increased plant biomass and so plant Hg content since Hg contents is a function of total biomass and Hg concentration. It can be concluded that based on the criteria of accumulator plant,kiambang is the most potentially Hg accumulator followed by genjer and eceng.Key words: Phytoextraction, Hg, Salvinia molesta, Limnocharis flava, Monochoriavaginalis